Penetração de cloretos em concretos com diferentes tipos de cimento submetidos a tratamento superficial - Crauss, Camila (2010)
The durability characteristics of concrete should be given the same importance as compressive strength when designing concrete structures. Concrete should be able to withstand the effects of aggressive agents and behave as a protective layer that can block the penetration of substances that could corrode the steel in concrete. The corrosion of reinforcing steel in concrete structures can be caused by factors such as carbonation and the action of chloride ions, which can penetrate the concrete through absorption and diffusion processes. When the concrete does not show resistance to chloride penetration, the use of surface treatment is required. This study investigates chloride penetration in concrete samples that received three different kinds of surface treatment: a single component polymer mortar applied in a 4-mm thick layer, a pore blocker with a single coat and a pore blocker with a double coat. The concrete samples used were produced with cement types CP IV 32, CP II F and CP V and compressive strength values of 15MPa, 20MPa and 25MPa. Chloride penetration was assessed using ASTM C 1202 and AgNO3 aspersion after immersion in a salt solution in concrete samples with and without surface treatment. Surface treatments like pore blockers were able to reduce the chloride flow inwards concrete due to the sealing effect in the superficial pore layer, caused by the reactions with the cement hydration products. The double treatment with pore blocker (XCM) showed to be more effective, providing bigger reduction in total passing charge. This reduction was greater in pozzolanic cements and in those with the lowest resistance, fck=15 MPa. The concrete produced with cements type CP II F and CP V showed bigger values of passing charge and diffusion coeficient. The use of polymeric mortar (Z4) with 4 mm thickness was considered the best alternative among those investigated. It produced the greatest reduction in total passing charge as well as the best efficiency in decreasing chloride penetration, and showed a good adherence in the concrete substratum and compactness.